Spin rectification by orbital polarization in Bi-bilayer nanoribbons. Issue 12 (7th March 2016) - Jin, Kyung-Hwan; Jhi, Seung-Hoon
Abstract : We investigate the edge states of quantum spin-Hall phase Bi(111) bilayer nano-ribbons (BNRs) and their spin-rectifying effect using first-principles calculations and the non-equilibrium transport method. Abstract : We investigate the edge states of quantum spin-Hall phase Bi(111) bilayer nano-ribbons (BNRs) and their spin-rectifying effect using first-principles calculations and a non-equilibrium transport method. As low-dimensional materials, BNRs have tunable electronic properties, which are not only dependent on the edge shape, chemical passivation, or external electric fields but also governed by geometrical deformation. Depending on the passivation types, the interaction of the helical edge states in BNRs exhibits various patterns, enabling the valley engineering of the Dirac cones. In addition, the spin texture of the Dirac state is significantly tuned by edge passivation, external electric fields and geometric deformations. We demonstrate that curved BNRs can be used as the spin valves to rectify the electric currents via the edge states. Our results provide a practical way of utilizing two-dimensional topological insulator Bi bilayers for spintronic devices.